Impact of Smartphone Addiction on Sleep Patterns in University Students in Pakistan - Raza, Nazia (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the impact of smartphone addiction on sleep patterns in university students in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on the impact of smartphone addiction on sleep patterns in university students in Pakistan reveals that excessive smartphone use significantly disrupts sleep quality and duration. Findings indicate that students with high smartphone addiction levels experience delayed sleep onset, reduced total sleep time, and increased sleep disturbances. The use of smartphones before bedtime, particularly for social media and gaming, correlates with poorer sleep outcomes and higher instances of insomnia. The research highlights that smartphone addiction is linked to increased sleep latency and diminished sleep efficiency. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), cognitive behavioral theory (CBT) & uses and gratifications Theory (UGT) may be used to anchor future studies on the impact of smartphone addiction on sleep patterns in university students in Pakistan. Universities should implement educational programs that raise awareness about the negative impacts of excessive smartphone use on sleep and overall well-being. Universities should establish policies that limit smartphone use in certain contexts, such as during lectures and in dormitories after certain hours.